2020
DOI: 10.18632/aging.103779
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an immune and stromal prognostic signature in uveal melanoma to guide clinical therapy

Abstract: The tumor microenvironment is known to play an important role in uveal melanoma. Reliable prognostic signatures are needed to aid high risk patients and improve prognosis. Uveal melanoma tissues from three public datasets were analyzed. RNA sequence data of uveal melanoma and corresponding clinical features were obtained from The Cancer Genome Atlas database. Immune and stromal scores were calculated by applying the “ESTIMATE” algorithm. The samples were divided into high and low immune or stromal score groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We also investigated the tumor microenvironment and found no statistically significant differences in the remaining immune score and tumor purity, except for the stromal score, which was higher in the MUC16 wild-type group. Thus, a higher stromal score seems to predict a worse prognosis, and Gong et al [ 20 ] also found that a higher stromal score was always associated with poor prognosis in patients with melanoma. mRNAsi in the MUC16 mutation and wild-type groups was also compared, and mRNAsi was found to be much higher in the mutation group than in the wild-type group.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the tumor microenvironment and found no statistically significant differences in the remaining immune score and tumor purity, except for the stromal score, which was higher in the MUC16 wild-type group. Thus, a higher stromal score seems to predict a worse prognosis, and Gong et al [ 20 ] also found that a higher stromal score was always associated with poor prognosis in patients with melanoma. mRNAsi in the MUC16 mutation and wild-type groups was also compared, and mRNAsi was found to be much higher in the mutation group than in the wild-type group.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a limited number of patients benefit from the currently available regimens [16]. This may be due to differences in tumor-infiltrating immune cells within the tumor microenvironment, which affect the clinical outcome in cancer patients by regulating immune escape [17,18]. In pancreatic and colorectal cancer, the expression of m6A regulators is related to tumor immune cell infiltration, providing certain cues for the therapeutic response of ICIS [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The scores represent tumor purity. In many malignant tumors such as primary gastric cancer [ 38 ] and uveal melanoma [ 39 ], the higher the score, the higher the purity of tumor cells and the worse the prognosis. Meanwhile, a higher immune score represents the more robust immune activity of the tumor so that patients may benefit from immunotherapy [ 40 ].…”
Section: Discussionmentioning
confidence: 99%